2015
DOI: 10.1097/scs.0000000000002180
|View full text |Cite
|
Sign up to set email alerts
|

A Novel System for Navigation–and Robot-Assisted Craniofacial Surgery

Abstract: The technical method of navigation-guided robotics system, allowing the operator to practice the virtual planning procedure through navigation system as well as perform the actual operation thru the robotic arm, could be regarded as a valuable option for benefiting craniofacial surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, the system was only studied for model experiments, and no further research and development was conducted for the robotic arm body and control system, which were mainly combined with the navigation system for system integration, and no further research was reported subsequently. 47 In 2008, Xia and colleagues reported a skull base drilling robot with an integrated Stealthstation navigation system, a 6-dimensional force sensor NeuroMate neurosurgical robot, and 3-dimensional display software that can operate in a safe space with virtual constraints on medical imaging data. The system was used for drilling experiments in the posterior external ear hole of a cadaver head, and postoperative computed tomography (CT) showed that it partially exceeded the falsely constrained space by 1 to 2 mm, up to 3 mm, but had good ergonomic results, such as stability of the drill bit.…”
Section: History Of Craniomaxillofacial Robotic-assisted Surgerymentioning
confidence: 99%
“…However, the system was only studied for model experiments, and no further research and development was conducted for the robotic arm body and control system, which were mainly combined with the navigation system for system integration, and no further research was reported subsequently. 47 In 2008, Xia and colleagues reported a skull base drilling robot with an integrated Stealthstation navigation system, a 6-dimensional force sensor NeuroMate neurosurgical robot, and 3-dimensional display software that can operate in a safe space with virtual constraints on medical imaging data. The system was used for drilling experiments in the posterior external ear hole of a cadaver head, and postoperative computed tomography (CT) showed that it partially exceeded the falsely constrained space by 1 to 2 mm, up to 3 mm, but had good ergonomic results, such as stability of the drill bit.…”
Section: History Of Craniomaxillofacial Robotic-assisted Surgerymentioning
confidence: 99%
“…Moreover, osteotomy for RBG includes cutting in various directions using various instruments [5]. Long-bone osteotomy, such as for a fibula free flap or Le Fort I osteotomy have better accessibility for the robot than the osteotomy for RBG, and are simple one-direction osteotomy examples [6,7]. Therefore, we needed to evaluate RBG osteotomy accuracy in various directions and categories.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Previous studies have demonstrated the effectiveness, precision, and safety of robot-assisted craniomaxillofacial surgery. [7][8][9] However, the main application of optical navigation systems, which are highly restricted by light, cannot meet the demands of mandibular distraction osteogenesis via an intraoral incisional approach in children with HFM. 10 Ensuring accurate registration and dynamic, intraoperative tracking of the robotic coordinates and target position is a major barrier in the clinical application of robotic surgery.…”
mentioning
confidence: 99%